Rural social infrastructure development in India : an inclusive approach - Mahadeva, M. (Diverse perspectives on creating a fairer society., 2024)
India, despite being largely rural, has struggled to maintain an adequate social infrastructure in its rural regions due to insufficient need-based development interventions, low public spending, limited market reach and a lack of individual contributions. Examining recent policy changes that are seeking to tackle these issues, Rural Social Infrastructure Development in India advocates for transformative change against the backdrop of poverty intervention and contemporary development discourse. Delving into a transformative journey focused on inclusive housing development and financial strategies, M Mahadeva celebrates and critically analyses milestones achieved in uplifting marginalised rural populations in India. Dissecting secondary data from official Indian authorities, the author scrutinises housing poverty, amenities deprivation and financial exclusion at both national and regional levels. Focusing on impactful programs like PMAY and PMJDY, chapters illuminate the interplay of public participation, political consensus and economic commitment in shaping rural social infrastructure. Aligned to the UN Sustainable Development Goals and emphasizing the pivotal roles of individuals, public authorities and strategic public investment, Mahadeva underscores the critical role of safe housing, sanitation and financial citizenship in fostering well-being and sustainable human settlements. A compelling call to action for development impact on a global scale, this mission-driven work brings us one step closer to building a more inclusive India.